2016
DOI: 10.5194/bg-13-2415-2016
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide and methane in two tropical estuaries in a peat-dominated region of northwestern Borneo

Abstract: Abstract. Estuaries are sources of nitrous oxide (N 2 O) and methane (CH 4 ) to the atmosphere. However, our present knowledge of N 2 O and CH 4 emissions from estuaries in the tropics is very limited because data are scarce. In this study, we present first measurements of dissolved N 2 O and CH 4 from two estuaries in a peat-dominated region of northwestern Borneo. Two campaigns (during the dry season in June 2013 and during the wet season in March 2014) were conducted in the estuaries of the Lupar and Sarib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 53 publications
(75 reference statements)
4
28
3
Order By: Relevance
“…The concentrations measured for this tropical mangrovedominated estuary (Figure 10) were within the range of that reported for other tropical estuaries located at west (113 ± 40 nM) and east (27 ± 6 nM) coast of India, such as Luper (5.2-59 nM) and Saribus (3.7-135 nM), as well as estuaries located in northwestern Borneo (Muller et al, 2016;Rao and Sarma, 2016). Seasonally, estuarine surface water CH 4 concentrations during post-monsoon (90.91 ± 21.20 nM) were significantly higher [p (= 0.01) < 0.05] compared to pre-monsoon (54.20 ± 5.06 nM) conditions.…”
Section: Distribution Of Dissolved Chsupporting
confidence: 83%
“…The concentrations measured for this tropical mangrovedominated estuary (Figure 10) were within the range of that reported for other tropical estuaries located at west (113 ± 40 nM) and east (27 ± 6 nM) coast of India, such as Luper (5.2-59 nM) and Saribus (3.7-135 nM), as well as estuaries located in northwestern Borneo (Muller et al, 2016;Rao and Sarma, 2016). Seasonally, estuarine surface water CH 4 concentrations during post-monsoon (90.91 ± 21.20 nM) were significantly higher [p (= 0.01) < 0.05] compared to pre-monsoon (54.20 ± 5.06 nM) conditions.…”
Section: Distribution Of Dissolved Chsupporting
confidence: 83%
“…In other words the potential N 2 O ventilation is higher than the observed N 2 O water-air flux, and any in situ production of N 2 O is overwhelmed by the river load. the spatial transect (Mueller et al, 2016). In the dry season however, Mueller et al (2016) found that N 2 O concentrations were less variable and most of the N 2 O came from upstream, freshwater inputs.…”
Section: Fitzroy River Estuary 320mentioning
confidence: 96%
“…the spatial transect (Mueller et al, 2016). In the dry season however, Mueller et al (2016) found that N 2 O concentrations were less variable and most of the N 2 O came from upstream, freshwater inputs.…”
Section: Fitzroy River Estuary 320mentioning
confidence: 96%
See 2 more Smart Citations